A study on issues and challenges of information technology act 2000 in India - Srinivasa Rao Dokku; Deenamma Kandula (Goodwood Publishing, 2021)
Purpose: This article focused on the jurisprudence of cyber law, how cybercrime is categorized in relation to regular crime, and the jurisdictional problems it raises. In India, the Information and Technology Act of 2000 primarily governs cybercrime. The Information and Technology Act of 2000's implementation problems and difficulties are also identified in this study. Research Methodology: The study's objectives were to understand the many cybercrimes that occur in India as well as the problems and obstacles related to them. The study is based on secondary data, and it analyses and interprets data from the last three years. The primary information was gathered through press publications, crime bureaus of investigation, etc. Results: In the past three years, the nation has reported over 16 lakh cybercrime incidences, and more than 32,000 FIRs have been filed in India since 2020. 8,829 instances were reported in Uttar Pradesh in 2021, down from 11,097 in 2020. Karnataka saw a decrease in instances from 10,741 in 2020 to 8,136 in 2021. 10,730 cybercrimes against women were reported in India in 2021. Out of this, the majority of instances were related to disseminating obscene sexual content or cyberpornography. 1,896 similar instances were reported in 2021. Limitations: This study is based on secondary information only. The data was collected from only secondary sources and from the last three years only Contribution: The policymakers, educators, and the general public will benefit from this study's explanation of cybercrimes in India. Additionally, it draws attention to the difficulties with the 2010 Indian Information Act.